Financial Literacy, Financial Behaviour and Financial Anxiety: Implication for Financial Well Being of Top Management Level Employees - Lidwina Friska Adriana Pijoh; Rhian Indradewa; Tantri Yanuar Rahmat Syah (Penerbit Kemala Indonesia, 2020)
This study aims to analyze how Financial Literacy, Financial Behaviour and Financial Anxiety influence Financial Well Being of Top Management Level Employees. A cross-sectional survey was employed on 256 respondents randomly selected from top management level of manufacture company. It then tests their hypothesized relationships with the use of Partial Least Squares (PLS), a structural equation modelling technique. The result reveal that financial behaviour and financial anxiety significantly influence the financial well-being of employee. Financial literacy also influences the financial anxiety, financial behaviour and financial well-being. Financial behaviour of an individual also determine the level of financial wellbeing of the respondents. Positive and healthy financial behavior leads toward the higher level of financial wellbeing. There is significant and positive effect of financial literacy to financial behaviour of top management level of employees.